L’ecdotique numérique à l’épreuve d’un manuscrit scolaire byzantin : décrire, déchiffrer et transcrire le Marcianus gr. XI, 1 - Laurent Capron; Julie Giovacchini; Sébastien Grignon (Humanités Numériques)
The authors aim to achieve a complete digital edition of the Greek manuscript XI.1 of the Biblioteca Marciana in Venice (= coll. 452). The first step was to identify as precisely as possible all the texts that appear in the various anthologies and compilations contained in this 14th-century school manuscript. Several of the anthologies are accompanied by grammatical and lexical scholia, known by a well-identified manuscript tradition and mostly used for the elaboration of a lexicon of Attic words. The difficulty of encoding this document in TEI-XML lies in the choice of the tags considered the most appropriate, since in TEI-XML scholia are considered as additions to the text, whereas here they seem to be a central element of the transmitted teaching. The authors propose a schema that allowed them to encode literary texts and scholia in an equivalent way but linked together, with unique identifiers.